2013
DOI: 10.7717/peerj.211
|View full text |Cite
|
Sign up to set email alerts
|

Amino-acid site variability among natural and designed proteins

Abstract: Computational protein design attempts to create protein sequences that fold stably into pre-specified structures. Here we compare alignments of designed proteins to alignments of natural proteins and assess how closely designed sequences recapitulate patterns of sequence variation found in natural protein sequences. We design proteins using RosettaDesign, and we evaluate both fixed-backbone designs and variable-backbone designs with different amounts of backbone flexibility. We find that proteins designed with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 37 publications
1
29
1
Order By: Relevance
“…As an alternative to predicting evolutionary variation from simple structural measures such as contact density or backbone flexibility, one can also predict evolutionary variation via a protein-design approach (Dokholyan and Shakhnovich 2001; Ollikainen and Kortemme 2013; Jackson et al 2013). In this case, one takes the protein structure of interest, replaces all residue side chains with randomly chosen alternatives, and uses a coarse-grained or atom-level energy function to assess which side-chain choices are consistent with the backbone conformation of the focal structure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As an alternative to predicting evolutionary variation from simple structural measures such as contact density or backbone flexibility, one can also predict evolutionary variation via a protein-design approach (Dokholyan and Shakhnovich 2001; Ollikainen and Kortemme 2013; Jackson et al 2013). In this case, one takes the protein structure of interest, replaces all residue side chains with randomly chosen alternatives, and uses a coarse-grained or atom-level energy function to assess which side-chain choices are consistent with the backbone conformation of the focal structure.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, one takes the protein structure of interest, replaces all residue side chains with randomly chosen alternatives, and uses a coarse-grained or atom-level energy function to assess which side-chain choices are consistent with the backbone conformation of the focal structure. We have recently used this approach to compare natural and designed sequence variability in cellular proteins (Jackson et al 2013), and we have found that (i) flexible-backbone design, where small backbone movements are allowed during the design phase, outperformed fixed-backbone design, and (ii) intermediate backbone flexibility, obtained via an intermediate design temperature, produced the highest congruence between designed and natural sequences. Similarly, Dokholyan and Shakhnovich (2001) had previously found that an intermediate temperature parameter gave the best agreement between designed and natural sequences in their model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations